Community Perceptions on Conservation, Livelihood Vulnerability and Quality of Life Around Tanzania’s Kilimanjaro National Park - Gasto Jerome Lyakurwa; Mercy Chepkemoi Chepkwony; Edwin Sabuhoro (Land)
This research examined the multidimensional relationship between the subjective quality of life, conservation attitudes, and livelihood vulnerability of communities surrounding the Kilimanjaro Mountain National Parks and Biosphere Reserve in Tanzania. Data were collected using a questionnaire survey in four villages bordering the Kilimanjaro National Park and analyzed using partial least square structural equation modeling. The results show that conservation attitudes increase and there are different levels of household livelihood vulnerability as the quality of life improves, indicating a positive relationship between the subjective quality of life and conservation attitude. People with higher livelihood vulnerability show a substantial increase in conservation attitudes as their quality of life improves. People with medium livelihood vulnerability show weaker but still positive relations between quality of life and conservation attitudes. However, when the livelihood vulnerability is lowest, the conservation attitudes change the least with improved quality of life. Furthermore, livelihood-vulnerable people tend to be more supportive of conservation than those with lower livelihood vulnerability, and this difference increases as the quality of life increases, indicating the significance of the quality of life in predicting conservation attitudes in highly vulnerable groups. These results are essential for managers and development practitioners, who focus on achieving win–win scenarios between conservation and development to enhance people’s overall quality of life rather than concentrating on reducing vulnerabilities.